EBV-Related Diffuse Large B-Cell Lymphoma in a Patient with Angioimmunoblastic T-Cell Lymphoma - Şimşek, Cem; Bostankolu, Başak; Özoğul, Ece; Sağlam Ayhan, Arzu; Üner, Ayşegül; Büyükaşık, Yahya (Turkish journal of haematology, 2019)
Angioimmunoblastic T-cell lymphoma (AITL) is a common subtype of peripheral T-cell lymphoma, accounting for approximately one-fifth of cases [1]. Epstein-Barr virus (EBV)- positive B cells are present in the tumor tissue in most cases [2]. Twenty-five cases of EBV-associated B-cell lymphomas in AITL patients have been reported in the literature [1,3,4,5,6,7,8,9,10, 11,12,13,14,15]; herein, we report the 26th case.